Hubungan Pemenuhan Kebutuhan Zat Gizi Makro pada Sarapan dengan Daya Konsentrasi Mahasiswa Ilmu Keperawatan STIKes Karya Kesehatan Kendari - Prasetya, Fikky; Baso, Asnawi (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
Breakfast is food eaten in the morning before activity, which consists of staple food and side dishes or snacks. Breakfast time starts from 06.00 am to 10.00 am. Among the benefits of breakfast is increasing physical endurance, work productivity and concentration power. This study aims to determine the relationship of meeting the needs of macronutrients at breakfast with the concentration power of nursing students of STIKES Karya Kesehatan Kendari. This research is a descriptive analytic study, with a cross sectional study design and was conducted on August 14-18 at STIKES Karya Kesehatan Kendari. The population is students of the nursing science study program STIKES Karya Kesehatan Kendari batch 2014-2016 as many as 146 people and a sample of 109 people. Data were obtained using a questionnaire and using the chi-square test. The results of this study showed that out of 109 people, there were 33 people (69.2%) who had their carbohydrate needs met and 74 people (30.8%) who didn't. in the sample whose carbohydrate needs were not met. Furthermore, there were 36 people (33.6%) who had their protein needs met and 71 people (66.4%) who were not met, then most (38.3%) had poor concentration. found in samples whose protein requirements were not met. Furthermore, there were 101 people (94.4%) whose fat needs were not met and only 6 people (5.6%) were met, then most (39.3%) who had poor concentration power were found in samples whose fat needs were not met. fulfilled. The conclusion in this study is that there is no relationship between meeting the needs of macronutrients (carbohydrates, protein, and fat) at breakfast with the concentration power of nursing students at STIKES Karya Kesehatan Kendari. concentration